Eradication of human papillomavirus and elimination of HPV-related diseases - scientific basis for global public health policies - Matti Lehtinen; Iacopo Baussano; Jorma Paavonen; Simopekka Vänskä; Joakim Dillner (Taylor & Francis Group, 2019)
Introduction: Infections with oncogenic human papillomaviruses (HPV) globally cause about 9% of cancers in females and 1% of cancers in males. HPV disease burden can be effectively controlled by prophylactic HPV-vaccination provided it has high impact. Areas covered: A unique series of biobank-based and health registry-based studies that exploit randomized intervention cohorts has provided data on population-level safety of HPV vaccination, duration of vaccine-induced protection and impact of gender-neutral HPV vaccination, providing a scientific basis for policies to eradicate oncogenic HPV types and associated diseases worldwide. Expert commentary: The ultimate goal of HPV vaccination is the eradication of high-risk (hr) HPVs. Seventy-five percent coverage gender-neutral vaccination of early adolescents will rapidly eradicate also HPV16 from the general population.